2019
DOI: 10.1103/physrevb.99.184425
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of spin diffusion length and spin Hall angle of the antiferromagnetic Weyl semimetal Mn3Sn

Abstract: Antiferromagnetic Weyl semimetal Mn3Sn has shown to generate strong intrinsic anomalous Hall effect (AHE) at room temperature, due to large momentum-space Berry curvature from the timereversal symmetry breaking electronic bands of the Kagome planes. This prompts us to investigate intrinsic spin Hall effect, a transverse phenomenon with identical origin as the intrinsic AHE. We report inverse spin Hall effect experiments in nanocrystalline Mn3Sn nanowires at room temperature using spin absorption method which e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 66 publications
1
33
0
Order By: Relevance
“…Recent developments in the thin film fabrication processes have led to the realization of various spintronic devices using the Mn 3 Sn film. [ 26–34 ] In the antiferromagnetic memory made of the Mn 3 Sn/heavy metal multilayers, the electrical current may switch the direction of the ferroic order of the magnetic octupole (Figure 1b). Thus, the information is stored as the polarity of AHE, which may be read out through the sign and magnitude of the anomalous Hall voltage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent developments in the thin film fabrication processes have led to the realization of various spintronic devices using the Mn 3 Sn film. [ 26–34 ] In the antiferromagnetic memory made of the Mn 3 Sn/heavy metal multilayers, the electrical current may switch the direction of the ferroic order of the magnetic octupole (Figure 1b). Thus, the information is stored as the polarity of AHE, which may be read out through the sign and magnitude of the anomalous Hall voltage.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic, transport, and structural properties of the Mn 3 Sn layer made by the same method have been reported previously in the previous studies. [ 27,34 ] Using the thin films, a Hall bar structure (16 μm × 96 μm) is fabricated, which is contacted with Ti/Au electrodes (Figure 1c). In our electrical switching experiment, both electrical current and bias field are applied along the longitudinal direction ( x ‐direction), and the transverse Hall voltage V H is detected in the y ‐direction.…”
Section: Introductionmentioning
confidence: 99%
“…A recent discovery of the large anomalous Hall effect (AHE) in noncollinear AFM Mn 3 Sn and related compounds, where the Hall signal is comparable to that of ferromagnetic (FM) materials, indicated the possibility of using these materials in memory devices with additional advantage of having almost no perturbing stray fields. [ 9–13 ] Mn 3 Sn possesses a Ni 3 Sn‐type hexagonal structure (space group P6 3 /mmc, number 194) and noncollinear spin configuration with AFM to paramagnetic phase transition at T N = 420 K. [ 14 ] A large AHE in Mn 3 Sn is correlated with a large momentum‐space Berry curvature due to the noncollinear triangular AFM spin structure. [ 15 ] In the hexagonal unit cell, each a – b plane involving a slightly distorted Kagome lattice of Mn moments with geometrical frustration displays itself as an inverse triangular spin structure (see inset of Figure for the geometrical atomic arrangement), which holds a very small magnetic moment.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, Liu et al found that AHE in Mn 3 Pt can be effectively tuned by a small strain due to the fragile magnetic order in this material . Apart from AHE, in 2019, the contribution of non‐collinear magnetic order in Mn 3 Sn to SHE was demonstrated by Kimata et al This newly discovered magnetic SHE can be manipulated by an external magnetic field, and the θ SH of Mn 3 Sn was evaluated to be ≈5.3 ± 2.4% by the inverse spin Hall measurement . These intriguing discoveries have deepened the comprehension of antiferromagnet spintronics and provided possibility for related applications.…”
Section: Modulation Of Hm/fm Interface For Low‐power Sot Switchingmentioning
confidence: 97%